PREDIKSI UMUR FATIK STRUKTUR CRANE KAPASITAS 10 TON MENGGUNAKAN METODE ELEMEN HINGGA - Lasinta Ari Nendra Wibawa (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2020)
The Crane is one of the heavy equipment in an industry. In the LAPAN Garut office, Crane is used for the rocket assembly process. The study examines the fatigue life prediction of Crane structures using the finite element method. Crane structure design uses Autodesk Inventor Professional 2017, while finite element analysis uses Ansys Workbench 2019 R1. Crane structure is subjected to a load of 10 tons with a fully-reserved type of loading. Fatigue life prediction using Gerber's mean stress theory. Crane structure material is Aluminum alloy. Simulation results show that the Crane structure has a minimum fatigue life of up to 1,971 x 106 cycles with a minimum safety factor of 1,106.